1997
DOI: 10.4319/lo.1997.42.2.0318
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pore‐water chemistry and physiology on the distribution of vesicomyid clams at cold seeps in Monterey Bay: Implications for patterns of chemosynthetic community organization

Abstract: Analyses of sulfide, methane, oxygen, and CO, in pore-water sampdes from three cold seep sites in Monterey Bay indicate that fluid chemistry is a strong determinant of the distribution of chemolithoautotrophic vesicomyid clams. The distribution of Culyptogena pacijca and Culyptogenu kilmeri were aligned closely with sulfide concentrations at all cold seeps and reflected species-specific capabilities for sulfide binding. Live clams occurred only in sediment where sulfide was detectable. Sulfide was not detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
114
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 26 publications
8
114
0
Order By: Relevance
“…The relationships between the concentration of methane and faunal distribution have been discussed both from the perspective of a toxin for animals and as a substrate for chemosynthetic production (e.g. Barry et al 1997). However, in general, faunal distribution in marine environments is explained by more generalized factors, such as temperature, salinity, and the concentration of DO.…”
Section: Faunal Zonation In a Vent Fieldmentioning
confidence: 99%
“…The relationships between the concentration of methane and faunal distribution have been discussed both from the perspective of a toxin for animals and as a substrate for chemosynthetic production (e.g. Barry et al 1997). However, in general, faunal distribution in marine environments is explained by more generalized factors, such as temperature, salinity, and the concentration of DO.…”
Section: Faunal Zonation In a Vent Fieldmentioning
confidence: 99%
“…Numerous studies have demonstrated that the flux of methane and sulfide towards the sediment/water interface determines the microbial and faunal community composition at cold seeps (e.g. Dando and Hovland, 1992;Barry et al, 1997;Sibuet and Olu, 1998;Sahling et al, 2002;Levin et al, 2003;Treude et al, 2003;van Dover et al, 2003;Arvidson et al, 2004;Levin, 2005;Niemann et al, 2006;Niemann et al, 2009;Lichtschlag et al, 2010a).…”
Section: Fischer Et Al: Pore Water Geochemistry Of Cold Seeps Offmentioning
confidence: 99%
“…This patchy distribution was found to be correlated with the fluid composition and flow rate (Niemann et al, 2006), reflecting distinct life requirements (required substrates or sensibility toward toxic compounds present in the fluids; Barry et al, 1997;Sibuet and Olu, 1998;Sahling et al, 2002;Niemann et al, 2006;Lichtschlag et al, 2010;Pop Ristova et al, 2012;Ruff et al, 2013).…”
mentioning
confidence: 99%